Pushing the boundaries: actual and potential distribution of thrushes expanding their ranges in South America - Vazquez, Miriam Soledad (2024)
The distribution of a species reflects its ecological adaptability and evolutionary history, which isshaped by the environment and represents a dynamic area subject to anthropogenic environmentalchange. We used the MaxEnt algorithm to construct ecological niche models for four thrushspecies within the Turdus genus; T. amaurochalinus, T. chiguanco, T. falcklandii and T. rufiventris.These models were used to predict the potential geographic distributions of these species thatare expanding their ranges in South America. Using occurrence records, we estimated currentlyoccupied areas for each species. We also identified suitable habitats and projected possible areas to becolonized by the four species at continental scale. Temperature annual range had the highest influencefor T. falcklandii, while human modification was the main variable explaining the distribution of theother three species. The potential distribution area ranged from 2.5 million km 2 for T. falcklandii tonearly seven million km 2 for T. amaurochalinus. Large proportions of suitable area remain unoccupiedby all four species, being 50% for T. amaurochalinus and T. rufiventris, and about 70% for T. chiguancoand T. falcklandii. Anthropogenic disturbances, such as habitat loss and ecosystem transformation,lead to non-random species extinction and biotic homogenization, highlighting the importance ofpredictive models as valuable tools for informing mitigation policies and conservation strategies.Thrushes are progressively expanding their ranges, and the colonization of new habitats could bringnew challenges.